Alex Ryan, stop that! - Mills, Claudia (New York : Farrar, Straus and Giroux, 2003)
Seventh-grader Alex Ryan enjoys attracting attention, though he never seems to impress his father, but when his antics cause problems with his would-be girlfriend on a school outing, he has second thoughts about his actions.
G5
Keywords: Schools -- Fiction; Interpersonal relations -- Fiction; Behavior -- Fiction; Fathers and sons -- Fiction